A Case of Traumatic Intractable Leg Ulcer with Lymphorrhea Diagnosed Using ICG Lymphography. Issue 3 (March 2021) - Osada, Atsuyoshi; Yamaki, Takashi; Kamei, Wataru; Yamamoto, Yusuke; Sakurai, Hiroyuki
Abstract : Summary: We report a case of traumatic lower extremity ulcers with lymphorrhea in a 37-year-old woman. She presented intractable ulcers without lymphedema for nearly 6 months after a traumatic injury. She was treated conservatively for 6 months at a referral hospital. Unfortunately, during conservative treatment, cellulitis was developed. Even though the inflammation resolved, the ulcer did not heal. We suspected persistent lymphorrhea as the cause of refractory ulcer, and for that reason, we performed indocyanine green lymphography. The lymphatic vessel damage site was identified; also, a collateral lymphatic vessel connected toward the central side was recognized. The lymph fluid drainage site was selectively ligated. The lymphorrhea and ulcers healed 1 month after ligation. Ulcers with lymphorrhea can be persistent and refractory to treatment. Indocyanine green lymphography can be a feasible diagnostic technique. It can identify the site of leakage and is thus useful for treatment. There are fewer reports on the evaluation of lymphorrhea with video presentation. Here, we report a case with video presentation.